Metric analysis of open access journals indexed in Scopus from 2019 to 2022: Orthopedics and Sports Medicine - Horta-Martínez, Lázaro Ernesto; Sorá-Rodriguez, Melissa; Rodríguez-Pereira, Yariadna (Revista Cubana de Información en Ciencias de la Salud, 2025)
Introduction: Scopus is considered, together with Isis Web of Science, one of the best databases, with a high prestige within this communication field. Objective: To characterize the 1st quartile journals of open access indexed in Scopus in the field of Orthopedics and Sports Medicine. Methods: A metric, descriptive and cross-sectional analysis of the open access journals indexed in Scopus belonging to the Orthopedics and Traumatology area was carried out, from 2019 to 2022. Results: A total of 26 journals were obtained; Of these, the highest CiteScore index corresponds to the Journal of Sport and Health Science with 15.7, while the highest number of citations corresponds to the Journal of Bone and Joint Surgery with 10,826 citations; the CiteScore mean is 6.4 ± 2.8 and citations is 2817.8 ± 2754.6. The sub-theme with the largest number of journals is Surgery with 12 (46.2%) and the one with the fewest journals is Anthropology with 3.8% (n = 1). Conclusions: The journals indexed in Scopus belonging to Q1 of the Orthopedics and Sports Medicine theme in the period from 2019 to 2022 have an average CitaScore of 6.4 and 2817.8 citations on average; published an average of 440 documents for 76.6% of citations, they belong mainly to the European continent with an average SNIP and SJR of 1,642 and 1,170 respectively, with Surgery being the most prevalent sub-theme and Springer Nature the most represented publisher.